SERICULTURE FARMERS’ PERCEPTION AND PERFORMANCE OF BOMBYX MORI AJ X AC HYBRID COCOON REARED WITH S30 MULBERRY LEAVES UNDER NIGERIAN TROPICAL CONDITION (FUDMA JOURNAL OF SCIENCES, 2020)
The study examined the sericulture farmers’ perception and the effects of S30 variety Mulberry leaves on the overall performance of the Bombyx mori L. AJ X AC Hybrid under the Nigerian tropical condition. A field survey of demographic status, Knowledge, Awareness and Perception (KAP) of sericulture practices was conducted using questionnaire and interview schedule. Also mulberry plant was cultivated and the leaves were used for feeding the reared silkworm. Evaluation of nature and characteristics of produced cocoon of silkworm was conducted. The result of the study revealed that majority of farming household heads 22(73.33%) and KWASU university staff 10(83.3%) fell between the age range of 31-50 years while the bulk of the students 24(96%) ranged between 20-30 years of age. The farming household head 10(33.3%), KWASU staff 10(83.3%) and all students respondents attended at least secondary education. KAP statements result indicated that bulk of the respondents (92.53%) were aware of government established sericulture centers, majority (95.52%) were cognizant of Mulberry plant leaves in feeding silkworm, 89% aware about rearing of silkworm and processing centers. About half of the respondents were either familiar with sericulture processes (52.23%) or participated in sericulture training (52.23%). The bulk of the sericulture respondents (74.63%) obtained their information about sericulture through informal sources, while (55.2%) got information from relatives and (32.8%) from extension agents. Based on the results of the study, the crossed variety (AJ X AC) has high quality, performed better in the parameters evaluated and recommended for adoption for quality silk production under Nigerian
Keywords: Silk worm, mulberry plant, rearing, KAP, cocoon